Respuestas
Respuesta dada por:
0
Hallar.
2b - 1 + 3a² = Si a = - 1/2 y b = 3
2 * 3 - 1 + 3( -1/2)² =
6 - 1 + 3( -1/2)( -1/2) =
5 + 3(1/4) =
5 + 3/4 =
(5*4)/4 + 3/4 =
20/4 + 3/4 =
(20 + 3)/4 =
23/4
Respuesta.
23/4
2b - 1 + 3a² = Si a = - 1/2 y b = 3
2 * 3 - 1 + 3( -1/2)² =
6 - 1 + 3( -1/2)( -1/2) =
5 + 3(1/4) =
5 + 3/4 =
(5*4)/4 + 3/4 =
20/4 + 3/4 =
(20 + 3)/4 =
23/4
Respuesta.
23/4
Respuesta dada por:
0
2 (3)-1+3 (-1/2)2=
6-1 -(3/2)(3/2)=
5-(1.5)(1.5)=
5-2.25=
2.75
6-1 -(3/2)(3/2)=
5-(1.5)(1.5)=
5-2.25=
2.75
Preguntas similares
hace 7 años
hace 10 años
hace 10 años
hace 10 años